2016
DOI: 10.1617/s11527-016-0976-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the casting process on the internal structure and physical properties of hemp-lime

Abstract: Bio-aggregate composites such as hemplime offer a more sustainable alternative to traditional walling infill material. Hemp-lime, whether in situ or prefabricated, is generally either cast or sprayed, which results in a directionally dependent, typically layered, physical structure. This paper considers the impact of compaction and layering on the directional thermal conductivity, compressive strength and internal structure of the material through use of a novel image analysis method. The results presented ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 23 publications
7
16
1
Order By: Relevance
“…It is not possible to read the material breaking stress. The same problem was noticed by Williams et al [ 1 ]. In the literature, the maximum stress is read at the point of transition from the elastic to plastic state [ 28 , 45 ].…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…It is not possible to read the material breaking stress. The same problem was noticed by Williams et al [ 1 ]. In the literature, the maximum stress is read at the point of transition from the elastic to plastic state [ 28 , 45 ].…”
Section: Resultssupporting
confidence: 74%
“…This may be due to the fact that the finer shives require more binders to achieve the desired consistency, resulting in an increased bulk density, which affects the value of the thermal conductivity coefficient. Williams [ 1 ] also showed that the thermal conductivity of the samples tested perpendicular to the direction of compaction is 16% higher than that of the samples tested in the parallel direction. Similar results are also described in [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a loose packing state, the particles are almost randomly oriented (geometric isotropy of the packing of particles). But under compression, the particles are increasingly oriented to lie flat, and tend towards a transverse isotropy, as shown by Williams et al (2016Williams et al ( , 2017 on lime and hemp composites. The weight coefficient in Eq.…”
Section: Thermal Behaviourmentioning
confidence: 97%
“…Unlike most previous studies that focused on hempcrete's mechanical, thermal, or moisture properties [10,23], this study experimentally estimated the mechanical strength (compressive and splitting tensile strength), thermal performance, and moisture regulation capabilities of eight hempcrete design mixes. Furthermore, in contrast to the existing studies that utilized a hemp/binder ratio of 1:2 or higher for wall formulas [18,26], this research focused on maximizing the hemp hurd ratio to improve the thermal properties of the hempcrete mixtures. Therefore, a hemp/binder ratio of 1:1 with a targeted density of 300 to 400 kg/m 3 was applied to create an insulating "infill wall" formula.…”
Section: Introductionmentioning
confidence: 99%